Analisis Kebutuhan dalam Penerapan Pembelajaran Berbasis Proyek Berbasis Teknologi untuk Mengajar Bahasa Inggris di Tingkat Universitas: Analisis Kebutuhan dalam Penerapan Pembelajaran Berbasis Proyek Berbasis Teknologi untuk Mengajar Bahasa Inggris di Tingkat Universitas - Kadek Agus Mahardika Yasa; Ni Nyoman Padmadewi; Kadek Sintya Dewi (Universitas Pendidikan Ganesha, 2023)
This research is needs research regarding the use of project-based learning. The purpose of this study is to compare the current situation and the expected situation regarding the use of Technology-Based Project-Based Learning at Monarch Singaraja. This study used an explanatory mix-method design where the mixed methods design was carried out by first analyzing the data quantitatively and then explaining it with qualitative methods. The quantitative method used is the questionnaire method which was given to ten English teaching lecturers at Monarch Singaraja. Qualitative analysis methods using interviews and document analysis. The document analysis method used is to analyze the syllabus, lesson plans, and learning sessions provided by the campus. The needs analysis method used is a combination research method between the CIPP model and the OEM model so that gaps can be found. In this study, it was found that the conceptual framework for using project-based learning had not been found. Another finding was that lecturers were pedagogically ready to carry out project-based learning, but were not ready in the form of paper or learning guides. The existence of a conceptual framework is very important to provide a foundation for lecturers in carrying out learning in the future so that learning can be carried out properly on this campus. Likewise, the readiness of lecturers and students in learning is needed so that this technology-based project-based learning can run optimally